Memorandum of understanding between Universiti Teknologi MARA and ZBW-Leibniz Information Centre for Economics (Germany) / Fakulti Perakaunan - Universiti Teknologi MARA, Fakulti Perakaunan (Universiti Teknologi MARA (UiTM), 2019)
Memorandum of understanding on collaboration for academic, cultural, scientific thought and personnel exchange.